Jewish Kulturbund in Bavaria, 1934-1938 - Smith, Dana, 1987- author.
1 online resource
Keywords: "This book provides a social and cultural history of Jewish art in Nazi Germany, with a focus on the Jewish artists, art critics, and audiences in Nazi Bavaria. From the time of its conceptualization in the autumn of 1933 until its final curtain call in November 1938, the Jewish Cultural League in Bavaria sustained three departments: music, visual arts, and adult education. The Bavarian example steps outside the highly professional cultural milieu of Jewish Berlin, and instead looks at relatively unknown efforts of Bavarian Jewish artists as they used art to define what it now meant, to them, to be Jewish under Nazism. Insightful and engaging, this book is ideal for advanced undergraduate students, graduate students, and scholars interested in social and cultural histories of Jews in Germany"--